A new super-twisting sliding mode control based direct instantaneous power control of PWM-rectifier connected to grid. (6th January 2022) - Fekik, Arezki; Denoun, Hakim; Hamida, Mohamed Lamine; Vaidyanathan, Sundarapandian; Yassa, Nacera
A new super-twisting sliding mode control (STSMC) based direct instantaneous power control (DPC) of pulse width modulation (PWM)-rectifier connected to grid is studied in this paper. The new STSMC-DPC scheme uses instantaneous power controllers. The new scheme does not use current controllers as with traditional vector control. The two regulators possess a design parameter that facilitates to adjust their behaviour between a linear operation of the PI type and a behaviour in conventional sliding mode with constant gain. Our tests demonstrate that STSMC-DPC shows a robust behaviour and that it functions without chattering in steady state as in a classical regulator. The results obtained are very relevant and satisfactory for the control of the PWM converter without sensor in terms of the reduction of the chattering as well as an operation under a power factor and having a low total harmonic distortion (THD) of the short absorbed and uncoupled control of the instantaneous powers.